Autonomous learning in reading class: Building the students’ independence character - Rahmawati, Ida Fitri; Wulyani, Anik Nunuk (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This article reports efforts to improve students’ reading ability in understanding narrative texts through the implementation of an autonomous learning strategy at SMPN 1 Singosari. The autonomous learning strategy was adopted in response to the current need for a learning process that supports the development of Indonesian students’ character. The study involved eighth-grade students of SMPN 1 Singosari during the 2010/2011 academic year. The findings indicate that the implementation of the autonomous learning strategy in reading activities effectively enhanced students’ comprehension of narrative texts. In addition, the strategy encouraged students to participate actively in reading activities and fostered independent learning behaviors.